Exploring issues on teaching and learning in Malaysian Private Preschools - Tee, Ying Qin; Md Nor, Mariani (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
The Malaysian government, as with the rest of the world is becoming increasingly aware of the importance of early childhood education towards nation building. This involves constant monitoring on the quality of preschool education. To improve the Malaysian preschool system, it is crucial to identify the issues encountered in the preschool teaching and learning in actual practice. Hence, this study aimed to explore the issues regarding teaching and learning in Malaysian private preschool settings. Three in-service preschool teachers from the Klang Valley were selected through purposive sampling. Data was collected through open-ended interviews. Observation was also carried out to triangulate the survey findings. Thematic analysis of the findings then resulted in four themes and eight sub-themes. Findings indicated the structured and formal preschool environment with excessive emphasis on academic outcomes, which contradict the established principles of developmentally appropriate practice (DAP) as well as requirements in the national preschool curriculum. Mismatch between teachers’ beliefs of the ideal practice and the actual practice was also discerned. Recommendations for stakeholders were included to tackle the identified issues towards developing a more conducive environment for the optimal development of Malaysian pre-schoolers. This present study will benefit policymakers, curriculum developers and relevant authorities related to early childhood education to catch a glimpse of the actual practice in many private preschools in Malaysia. Most importantly, it is hoped that this study would be a platform for a revamp in the Malaysian preschool education towards a more effective and holistic education for all Malaysian pre-schoolers.